Gender Differences in Networking of Slovenian SME’s - Karin ŠIREC; Katja CRNOGAJ (Revista de Management Comparat International)
Today, there is an indisputable fact that entrepreneurial (business) success derives from the establishment of mutual connection and cooperation, thereby presenting the essence of economic activities. The so-called networking economy has come to the forefront and is reflected in the networking activities of organizations, companies, and entrepreneurs. This paper investigates networking activities between enterprises and organizations (business networking) as well as entrepreneurs’ personal networking (entrepreneurial networking). Fundamental research question is: Does networking in Slovenian small and medium-sized companies’ differ between male and female entrepreneurs and the companies they are directing? The empirical research revealed interesting findings with regard to certain differences among Slovene SMEs with respect to gender (male versus female). Meanwhile, the research identified linkages between investigated dimensions—namely, entrepreneurs’ personal networking and business networking. Although significant domestic and international literature considers networking to be extremely important for enterprises’ and entrepreneurs’ success, it can be concluded that this is a relevant research topic. Companies as well as entrepreneurs can no longer be successful as individuals because the new information economy is driven by the economics of networks.